1990
DOI: 10.1007/bf01289345
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a real tensor potential in the inelastic scattering of 800 mev polarized protons from20ne using the dirac phenomenology

Abstract: Coupled-channel calculations using the Dirac phenomenology have been performed to analyze cross-sections and analyzing powers data for inelastic scattering of 800 MeV polarized protons from low-lying states in g~ Good agreement with the data has been obtained by using a real tensor potential V~ = 27.02 MeV, in addition to real scalar potential and complex vector potential. Deformation parameters obtained at this energy of 800 MeV are very close to those obtained at an energy much lower (24.5 MeV). Once more, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The tensor potential, which has been found to be very small compared to the scalar or vector terms has been neglected in (1) at least in the initial search procedure. We confirm this observation from the present study presented in this paper, where indeed the tensor term has been found to have a negligible effect on the data but with the exception however for the 2~ nucleus where the presence of such an UT term was required to improve substantially the fits to 800 MeV polarized protons scattering data mainly for Ay(O) for the 0 +, 2 +, 4 + states [13] in this nucleus. All data (a(0) and Ay(O)) were analyzed in the same way.…”
Section: U= Ur F (R R R A)+ I Ui F (R R I Ai)supporting
confidence: 92%
See 2 more Smart Citations
“…The tensor potential, which has been found to be very small compared to the scalar or vector terms has been neglected in (1) at least in the initial search procedure. We confirm this observation from the present study presented in this paper, where indeed the tensor term has been found to have a negligible effect on the data but with the exception however for the 2~ nucleus where the presence of such an UT term was required to improve substantially the fits to 800 MeV polarized protons scattering data mainly for Ay(O) for the 0 +, 2 +, 4 + states [13] in this nucleus. All data (a(0) and Ay(O)) were analyzed in the same way.…”
Section: U= Ur F (R R R A)+ I Ui F (R R I Ai)supporting
confidence: 92%
“…Moreover these CC Schr6dinger equation calculations have shown that the actual value of/?6 has little if not no effect on the measured 0 + -2 + -4 + cross-sections as was presented by Blanpied et al [ 11] for 2~ and Recently however, a reanalysis of the cross-sections and analyzing powers data for inelastic scattering of 800 MeV protons from the 0 + -2 + -4 + states of the K= 0 + band in 2~ in the framework of the CC formalism using the newly Dirac phenomenology has shown surprisingly clear evidence for a large /36 in the ground state of 2~ (/36 = -0.12) in good agreement with the former low energy results (Ep= 24.5 MeV) but in disagreement with the Schr6dinger CC analysis for these 800 MeV protons data [13].…”
Section: Pacsmentioning
confidence: 55%
See 1 more Smart Citation